Descriptive Analysis of Patients Living With HIV Affected by COVID-19. (1st October 2020) - Gudipati, Smitha; Brar, Indira; Murray, Shannon; McKinnon, John E.; Yared, Nicholas; Markowitz, Norman
Abstract : Background: COVID-19 disease has spread globally and was declared a pandemic on March 11, 2020, by the World Health Organization. On March 10, the State of Michigan confirmed its first 2 cases of COVID-19, and the number of confirmed cases has reached 47, 182 as of May 11, 2020, with 4555 deaths. Setting: Currently, little is known if patients living with HIV (PLWH) are at a higher risk of severe COVID-19 or if their antiretrovirals are protective. This study presents epidemiologic and clinical features of COVID-19 infected PLWH in Detroit, Michigan. Methods: This is a case series that included 14 PLWH with laboratory-confirmed COVID-19 infection who were evaluated at Henry Ford Hospital in Detroit, Michigan, between March 20, 2020, and April 30, 2020. Results: Fourteen PLWH were diagnosed with COVID-19. Twelve patients were men and 2 were women; 13 patients were virally suppressed. Eight patients were hospitalized, and 6 patients were told to self-quarantine at home after their diagnoses. Three patients who were admitted expired during their hospital stay. No patient required bilevel positive airway pressure or nebulizer use in the emergency department, and none developed acute respiratory distress syndrome, pulmonary embolism, deep venous thrombosis, or a cytokine storm while on therapy for COVID-19. Conclusion: Although the clinical spectrum of COVID-19 among PLWH cannot be fully ascertained by this report, it adds to the data that suggest that HIV-positive patients with SARS-CoV-2 infection are not at a greater risk of severe disease or death as compared to HIV-negative patients.